The impact of financial literacy, financial technology, social environment, and lifestyle on financial management - Dessy Novitasari Laras Asih; Very Andrianingsih; Moh. Faisol (Jurnal Akademi Akuntansi)
Purpose: This study aims to determine the influence of financial literacy, financial technology, social environment, and lifestyle on the financial management of college students.